2013
DOI: 10.1007/s12010-013-0554-y
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl Diselenide-Loaded Nanocapsules: Preparation and Biological Distribution

Abstract: Over the past years, organoselenium compounds have been aimed as targets of interest in organic synthesis. Diphenyl diselenide [(PhSe)2] is an important example of this class showing several pharmacological properties. However, the poor water-solubility and its low oral bioavailability may be considered an obstruction for the clinical utility of this compound. For this reason, the use of nanocapsules is a prominent approach to increase the bioavailability of lipophylic molecules. This study aims to prepare dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…13 In addition, our results established that DPDS-NCS in all tested doses did not present any significant effect on the GSH and GSSG levels in the brain and liver, indicating that even if the thiol groups of the compound are oxidized, normal levels can reestablished.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…13 In addition, our results established that DPDS-NCS in all tested doses did not present any significant effect on the GSH and GSSG levels in the brain and liver, indicating that even if the thiol groups of the compound are oxidized, normal levels can reestablished.…”
supporting
confidence: 52%
“…9,24 Additionally, DPDS-NCS was previously characterized as macroscopic homogeneous aspect, as well as submicronic sizes, low polydispersity indices, negative zeta potentials, and slightly acid or neutral pH values. 13 Giordani et al also demonstrated that nanoencapsulation improves the DPDS-NCS pharmacokinetics when compared to the free DPDS.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations